DETERMINANTS OF FOOD SECURITY IN ALGERIA IN LIGHT OF CLIMATE CHANGE-ANALYTICAL ECONOMETRIC STUDY FOR THE PERIOD 1990-2021 - Noureddine, Berber; Lemya , Mekarssi; Fatma Zohra, Boughari (The journal of contemporary issues in business and government, 2024)
This study aimed to identify the most important factors and variables that affect food security in Algeria in light of climate changes. The study approach includes econometric analysis based on the bound testing approach (ARDL) regarding the period of 1990-2021. The empirical study showed that rainfall does not contribute to increasing agricultural production in the long term, but rather the contribution is limited to the short term only. Therefore, enhancing and sustaining Algerian food security in light of the decline in rainfall requires ensuring water security by enhancing investments to benefit from underground and surface water. Desalinating seawater and directing it to agriculture; Strengthening national governance of food security and nutrition through a clear and shared vision of goals and means of action; Support sustainable agri-food sectors to create decent job opportunities in rural areas.